Ecowas common currency: How prepared are its members? - Sagiru Mati; çIrfan Civcir; Hüseyin Ozdeser (Investigación Económica, 2019)
This study operationalizes the Optimum Currency Area (OCA) to investigate the preparedness of Economic Community of West African States (ECOWAS) members to form a Monetary Union (MU). Inflation and output models are estimated, with the sample 1988:01 to 2017:12 for the former and 1967 to 2016 for the latter. Analyses of ECOWAS convergence criteria, impulse responses, variance decompositions and correlations of shocks of these two models, reveal that the shocks across the ECOWAS members are asymmetric. The conclusion is that ECOWAS members as a whole are not well-prepared and therefore a full-fledged pan-ECOWAS MU is not advisable. It is also found that members of the European Monetary Union (EMU) tend to be a better fit for OCA than the ECOWAS members. The study recommends various courses of action such as fostering coordination among Central Banks of ECOWAS members, and providing a fund to serve as an incentive for countries that may incur cost rather than benefit if the single currency is created.
Keywords: C13; E31; E52; E58; F33; F42; 330; Optimal Currency Area; ECOWAS; EMU; structural VAR; Blanchard-Quah decomposition